Impacts of Diagnosis-Related Groups Payment on the Healthcare Providers’ Behavior in China: A Cross-Sectional Study Among Physicians - Zhang L; Sun L (Dove Medical Press, 2021)
Lingli Zhang,1,2 Lihua Sun1 1College of Business Administration, Shenyang Pharmaceutical University, Shenyang, People’s Republic of China; 2Department of Pharmacy, Jinling Hospital, Nanjing, People’s Republic of ChinaCorrespondence: Lihua SunCollege of Business Administration, Shenyang Pharmaceutical University, No. 103 Wenhua Road, Shenyang, 110016, People’s Republic of ChinaTel +86 24 2398 6553Email slh-3632@163.comPurpose: Currently, China is piloting diagnosis-related groups (DRG) payment system in 30 cities. The main aim of this study was to explore the respondents’ impressions regarding the hospitals’ policies and physicians’ behavior change brought by the DRG payment system, and investigate whether and how the hospitals’ policies affect the physicians’ behavior.Methods: We distributed questionnaires designed for this study to 200 physicians. Data analysis consisted of descriptive statistics, T-test, and network analysis.Results: Respondents stated that the hospitals had adopted several policies in response to DRG payment and DRG payment could reduce overtreatment and improve efficiency. However, it also led to several negative effects including an increased explanation to the patients, hindering new technologies, case splitting, and cherry picking. In addition, there was no evidence that harmful effects such as refusing patients and premature discharge existed. Overall, the benefits outweighed the drawbacks of DRG. Moreover, the hospitals’ policies could effectively change physician behaviors. Our results indicated that promoting the implementation of clinical pathways had the most positive impact, while limiting costs and length of stay is not recommended.Conclusion: In general, Chinese physicians who participated in the questionnaire possessed relatively positive attitudes towards the DRG payment system. Nevertheless, some of the negative impacts cannot be ignored. Meanwhile, the hospitals’ policies should be implemented with adequate consideration of the impact on physicians’ behavior.Keywords: diagnosis-related groups, providers’ behavior, payment system reform, China